PENGARUH KUALITAS PELAYANAN DAN PENETAPAN HARGA TERHADAP KEPUASAN KONSUMEN (STUDI KASUS PADA HOTEL NEW HOLLYWOOD PEKANBARU) - ", Sumadi; Karneli, Okta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research was conducted at the Hotel New Hollywood Pekanbaru, located in the heart of Pekanbaru precisely located on the street No. Kuantan Raya. 120 Pekanbaru. The rapid development of the number of hotels is a serious problem for the hotel business. Increasingly high business competition causes a shift in marketing patterns in expanding its market share. The tight business competition greatly affects the sales of hotel room services. This has an impact on Pekanbaru New Hollywood Hotels in the sale of hotel room services.The purpose of this study was to determine the effect of service quality and pricing on consumer satisfaction at Pekanbaru New Hollywood Hotel. In this research the method used is quantitative descriptive with SPSS program. The population in this study were consumers at the New Hollywood Hotel Pekanbaru 32,046. Samples taken using the Slovin formula, amounting to 100 respondents. Hypothesis testing uses simple linear analysis and multiple linear analysis by showing the results that service quality and pricing have a significant effect on customer satisfaction at the Hotel New Hollywood Pekanbaru. By calculating the coefficient of determination (R 2 ) simple quality of service to customer satisfaction R-square values obtained for 0308, or 30.8%, and the quality of service to customer satisfaction obtained value of R square of 0360 or 36%. Calculation of multiple determinations of service quality and price determination of customer satisfaction obtained an R square value of 0.409. This shows that the percentage of the contribution of the influence of service quality and pricing variables on customer satisfaction by 40.9% while the remaining 59.1% is influenced by other variables that the researchers did not mention in this study. Keywords: Service Quality, Pricing and Consumer Satisfaction